Biochar enhances seed germination and crop early growth for sustainable agriculture in Bangladesh - Md Rezaul Karim; Sonchita Biswas; Md Abdul Halim; Romel Ahmed (PLoS ONE, 2025)
Biochar (BC) application to low-fertility soils enhances crop yield, soil quality, and sustainable agricultural production. Although many studies have explored the effects of biochar on tropical crops, research specific to Bangladesh is limited. Given the agrarian system in Bangladesh, dense population, and vulnerability to climate change, adopting sustainable agricultural practices is essential. This study evaluates the impact of different biochar dosages on the germination and early growth of five major crops Oryza sativa (rice), Triticum aestivum (wheat), Capsicum annuum (chili), Solanum melongena (eggplant), and Solanum lycopersicum (tomato) using Acacia auriculiformis wood-waste biochar. The research was conducted using a randomized complete block design (RCBD) in a nursery setting. Biochar treatments of 10 t/ha and 15 t/ha were applied, with assessments made of germination (%), germination rate (after 7 days), shoot height (cm), root height (cm), leaf number, and root-shoot dry weight ratio. The results indicated a significant (p < 0.001) increase in germination (%) with higher biochar application rates. The linear mixed-effects model showed a significant effect of biochar treatment on germination (%) (F = 57.33, p < 0.001) and a significant interaction with crop type (F = 15.84, p < 0.001). In C. annuum, the 15 t/ha treatment resulted in a 96% increase in germination compared to the control (43.3 ± 1.08% vs 85.1 ± 2.15%). Similarly, in O. sativa, germination was significantly higher with the 10 t/ha (84.5 ± 1.52%) and 15 t/ha (91.8 ± 1.49%) treatments compared to control (59.3 ± 2.38%). Biochar significantly (p < 0.05) influenced early germination rates (after 7 days) and early growth parameters (e.g., shoot length, leaf count, root-shoot ratio), with the 15 t/ha treatment showing substantial improvements for C. annuum and O. sativa, while no significant effects were observed for S. lycopersicum. These findings underscore the potential of A. auriculiformis in enhancing germination and early growth of economically important crops, highlighting its role in promoting sustainable agriculture in Bangladesh.